A problemática da saúde na sociedade capitalista e suas implicações no processo de adoecimento dos trabalhadores brasileiros - Mendonça, Henrique Pereira Freitas de (2017)
This research seeks to analyze the process of sickness of Brazilian workers from the workhealth relationship in capitalist society. This is a bibliographical and documentary research carried out under the Marxist historical-critical theoretical perspective. It was found that the process of exploiting the workforce to reduce the necessary working time and reproduction of the process of accumulation of capital results in the sickness of the workers as much related to their work activity as in the other dimensions of their life. In Brazil, this condition is exacerbated by the recent process of industrialization and urbanization, which has led to a process of epidemiological transition that coincides with old forms of illness resulting from the historical development of the country, with new forms corresponding to economic modernization. It is observed that the fulfillment of the demands of capital and not of human needs is the root for not only the sickness related to work, but for the sickness of the worker in other spheres of life and that overcoming this problem implies overcoming the mode Of capitalist production.